P. Merime’s Essay “Nikolai Gogol” - T. Yu. Boyarskaya (Научный диалог, 2021)
Merimee’s essay “Nikolai Gogol”, in which the author presented the Russian writer as an imitator of European models, a satirist who focused on portraying the flaws of Russian life, a writer who neglects the plausibility of the overall composition is considered in the article. The author of this article shows that such a superficial and biased approach to Gogol’s texts aroused indignation among Russian journalists in both 19th century capitals and continues to be criticized by Russian and French literary critics. The results of a comparative analysis of the essay “Nikolai Gogol” with reviews of French-speaking journalists who wrote about the author of “The Inspector General” and “Dead Souls” in Parisian magazines of the 1840s are presented in the article. The question is raised that the motives that prompted Merimee to turn to the work of Gogol, and the reasons for the bias in relation to his work are still unrevealed. The novelty of the research is seen in the fact that the essay by Mérimée is for the first time considered as a commentary on the stable aesthetic position of the French writer, discordant with the poetics of romanticism and realism. The author dwells on the study of a number of artistic devices of the works of Merimee in the 1820—1840s and his genre preferences in the 1850s.